John - Stewart, Bryan A., 1973-; Thomas, Michael A., 1970- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2018)
The Church's Bible series brings the rich classical tradition of biblical interpretation to life, illuminating Scripture as it was understood during the first millennium of Christian history. Compiled, translated, and edited by leading scholars, these volumes draw extensively from early and medieval commentators. The Church's Bible leads contemporary clergy, Bible teachers, and students of Scripture into the inexhaustible spiritual and theological world of the early church.This volume on the Gospel of John contains select, freshly translated excerpts from the writings of such church fathers as Cyril of Alexandria, Cyril of Jerusalem, Gregory the Great, Theodore of Mopsuestia, Augustine, and Athanasius. Ranging chronologically from the second century to the ninth century, these patristic selections provide wide exposure to the breadth of the interpretive tradition on the Gospel of John.
Includes bibliographical references and indexes.
Keywords: Criticism, interpretation, etc. -- History -- Early church, ca. 30-600.; Criticism, interpretation, etc. -- History -- Middle Ages, 600-1500.